Gender Roles and Racial Influence in Zora Neale Hurston’s Their Eyes Were Watching God 1937 - Labbi, Sad Laaib, Nour Djinene Nadjela; Hasassa, Soundes (university of El-Oued, 2020)
The study under investigation examines the gender roles in Their Eyes Were Watching God (1937) by the eminent African American author, Zora Neale Hurston. It attempts also to trace the racial segregation among the African American community. This research aims to explore the nature of gender relations and women's undervaluation as well as the supremacy norms in the African American society through analyzing the journey of the protagonist “Janie” to identify her self-worth and independence. The study conducts a descriptive analytical method depending on the feminist theory to demonstrate the male gaze and feminine oppression. This study reveals that male dominance can be expressed variously throughout Janie's marriages; however, women themselves can see the traditional gender relations as necessary and worthwhile. Furthermore, Janie's realization of her self worth, independence, and voice are affected by her gender as a woman and her skin color as black. تفحص الدراسة الحالية الأدوار التقليدية للجنسين في "عيونهم كانت تراقب الله" ( البارزة، زورا نيل هيرستون. كما تحاول تتبع التمييز العنصري في المجتمع الأمريكي الافريقي . يهدف هذا البحث إلى استكشاف طبيعة العلاقات بين الجنسين والاستخفاف بالمرأة وكذلك معايير السيادة في المجتمع الأمريكي الأفريقي من خلال تحليل رحلة بطلة الرواية "جاني" لتحديد قيمتها الذاتية واستقلالها. تتخذ اً ا اعتماد ً ا وصفي ً ا تحليلي ً الدراسة منهج على النظرية النسوية لإثبات النظرة الذكورية والقهر الأنثوي. تكشف هذه الدراسة أنه يمكن التعبير عن هيمنة الذكور بأشكال مختلفة خلال زيجات جاني ؛ ومع ذلك ، يمكن للمرأة نفسها أن ترى العلاقات التقليدية بين الجنسين ضرورية وجديرة بالاهتمام. علاوة على ذلك، فإن إدراك جاني لقيمتها الذاتية واستقلالها وصوتها يتأثر بجنسها كامرأة ولون بشرتها الأسود.
Keywords: gender roles, racial segregation, African American community, feminist theory; أدوار الجنسين ، التمييز العنصري ، المجتمع الأمريكي الأفريقي ، النظرية النسوي.